2021
DOI: 10.25082/amler.2021.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The management of Digital Learning Objects of Natural Sciences and Digital Experiment Simulation Tools by teachers

Abstract: In the present study, we tried to find possible obstacles that Primary and Secondary education teachers face when managing Digital Learning Objects (DLOs) and/or Digital Simulation Tools (DST) in Science. One hundred seventy-six teachers from all over Greece answered the questionnaire. The results showed that the main reason for refusing to deal with DLOs and DSTs is the technological equipment. Also, the lack of adequate training level B 'results in about 25% of teachers not knowing the DSTs and 30% not knowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 36 publications
(37 reference statements)
5
72
0
Order By: Relevance
“…Furthermore, teachers do not trust the content of the curriculum as it is competent enough in digital tools, leading to the need of researching for appropriate learning object. This process introduce complications such as time consumption, insecurity, fear that these tools do not fit their teaching subject and more (Poultsakis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, teachers do not trust the content of the curriculum as it is competent enough in digital tools, leading to the need of researching for appropriate learning object. This process introduce complications such as time consumption, insecurity, fear that these tools do not fit their teaching subject and more (Poultsakis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Having conducted the research, we distinguished another issue: digital skills to work with technical teaching tools [21]. Most students acquired these skills whilst studying at secondary schools; however, there were those who had considerable difficulties whilst connecting to Zoom and working in Moodle.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that early childhood environments are rich in opportunities for children to be involved in STEM, and sciences can be naturally integrated with mathematics and/or technologies through the activity of the child (Campbell et al, 2018). Additionally, a lot of studies (Bers, 2017(Bers, , 2018Chen et al, 2017;Leonard et al, 2016) have shown that while participating in construction-based robotics activities, young children may be interested not only in many aspects of robotics but also in learning many programming and computational thinking features (Poultsakis et al, 2021). More particularly, the use of robotics affects positively the development of skills related to STEM learning, such as measurement with non-standard units (Solomon et al, 2015), coding (Papadakis, 2020), relationship analysis (Kazakoff et al, 2013), interpretation of graphs (Mitnik et al, 2009).…”
Section: Stem In Early Childhoodmentioning
confidence: 99%